Assessment for Measuring Computational Thinking Ability in Early Childhood - Widya Dwi Hardiyanti; Prayitno; Amir Syamsudin (Jurnal Pendidikan Anak Usia Dini Undiksha, 2026)
Computational thinking is an essential 21st-century competency that needs to be developed from an early age to support logical, systematic, and problem-solving skills. However, early childhood education teachers still face difficulties in assessing these skills due to the limited availability of validated assessment instruments. This study aims to analyze the computational thinking abilities of children aged 5–6 years using a valid and reliable assessment instrument. The study employed a descriptive quantitative approach involving 46 children aged 5–6 years selected through convenience sampling. Data were collected through performance tests based on the aspects of algorithms, debugging, decomposition, and pattern recognition. The instrument was tested using Aiken’s V, Pearson Product Moment, and Cronbach’s Alpha. Data were analyzed using descriptive statistics. The findings showed that most children’s computational thinking abilities were in the moderate category. The algorithms aspect was the most dominant ability, while debugging showed the lowest achievement. These findings indicate the need for stimulation through problem-solving-based learning and interactive media appropriate to children’s developmental stages. The implications of this study highlight the importance of using valid assessment instruments as a basis for designing learning activities to develop 21st-century skills in early childhood education.